Restoring spermatogenesis via the antioxidant properties of Moringa oleifera and Hibiscus sabdariffa in obesity-induced male rats - Nurul Shaqiinah Daaniah Jamaludin,; Nour Athiroh Abdoes Sjakoer,; Mahanem Mat Noor, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study aimed to assess the impact of aqueous extracts from Moringa oleifera (MO), Hibiscus sabdariffa (HS), and its combination (MOHS) on testicular cell development in male rats with obesity. Thirty-six male Sprague Dawley rats were divided into control and treatment groups. The control groups comprised normal, negative (obesity-induced rats, without treatment), and positive (obesity-induced rats, receiving 10 mg/kg orlistat) control rats. Meanwhile, the treatment group consisted of obesity-induced rats treated with herbal extracts: the MO400 group (received 400 mg/kg MO), HS150 group (received 150 mg/kg HS), and MOHS group (received a combination of 400 mg/kg MO and 150 mg/kg HS). All groups except the normal control group were fed a high-fat diet (HFD) until the Lee Obesity Index exceeded 310, followed by 38 days of treatment. Histological examination of the testes revealed positive effects of all herbal extracts on treatment, including active spermatogenesis with a high density of spermatogenic cells in the seminiferous tubules. The MOHS treatment significantly increased the diameter of seminiferous tubules compared to the negative control group (P<0.05). Moreover, the MOHS treatment exhibited the highest superoxide dismutase (SOD) enzyme activity compared to all groups (p<0.05) and lower malondialdehyde (MDA) levels compared to the negative control group. Meanwhile, the MO400 and HS150 treatment groups significantly reduced the Lee Obesity Index (p<0.05) compared to the control groups. In conclusion, MO and HS extracts, and their combination have demonstrated significant effects in improving male fertility parameters (spermatogenesis) and reducing the Lee Obesity Index by alleviating oxidative stress associated with obesity, thus supporting their potential as natural supplements to counteract obesity-induced infertility.